Mobile Device-Related Neck Pain as a Limiting Factor for Sport Participation in Young Adults - Jasiński, Filip; Bieniak, Magdalena; Kubiaczyk, Maja; Owczarek-Danowska, Iga Maria; Mamczak , Maria; Paluszek, Agnieszka Wiktoria; Michalik, Martyna (Quality in Sport, 2026)
Background Regular physical activity plays an important role in maintaining health among young adults. Nevertheless, musculoskeletal symptoms affecting the cervical region may limit engagement in sport and exercise. The growing use of smartphones is associated with prolonged static postures that can contribute to cervical discomfort and functional limitations. Such symptoms may influence training quality, range of motion and the overall level of sport participation. Aim The aim of this review was to evaluate the potential relationship between cervical musculoskeletal pain associated with prolonged mobile device use and sport participation among young adults. Material and methods This study is based on a narrative review of literature examining the association between mobile device use, neck pain and participation in physical activity. The literature search included databases such as PubMed, Scopus and Google Scholar. Studies published between 2017 and 2025 addressing posture-related issues, cervical discomfort and physical activity participation were included in the analysis. Results The analyzed studies indicate that prolonged smartphone use is commonly associated with forward head posture, cervical muscle fatigue and reduced neuromuscular efficiency. These factors may contribute to discomfort during sport activities and may discourage regular training. Conclusions Cervical discomfort related to prolonged mobile device use may represent a modifiable factor influencing sport participation. Preventive strategies including ergonomic education, postural awareness and cervical strengthening exercises may help support sustained engagement in physical activity.